2008
DOI: 10.1074/mcp.m700052-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Arabidopsis Cytosolic Ribosome Proteome Provides Detailed Insights into Its Components and Their Post-translational Modification

Abstract: Finding gene-specific peptides by mass spectrometry analysis to pinpoint gene loci responsible for particular protein products is a major challenge in proteomics especially in highly conserved gene families in higher eukaryotes. We used a combination of in silico approaches coupled to mass spectrometry analysis to advance the proteomics insight into Arabidopsis cytosolic ribosomal composition and its post-translational modifications. In silico digestion of all 409 ribosomal protein sequences in Arabidopsis def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
253
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(263 citation statements)
references
References 64 publications
9
253
1
Order By: Relevance
“…By 2006, our laboratory had found evidence for five added methyl groups on the large ribosomal subunit yeast protein Rpl12ab near the N-terminus; modification at Lys-3 by a SET-domain methyltransferase designated Rkm2 and by a yet unidentified enzyme at Lys-10 (44). However, these results were called into question by reports on the modifications of the orthologs of Rpl12ab in Arabidopsis thaliana (51) and Schizosaccharomyces pombe (52); both reports suggested that our mass spectrometry data was more consistent with the dimethylation of the N-terminal proline residue and the trimethylation of Lys-3 in line with the similar N-terminal modification of the Arabidopsis and S. pombe proteins. Further analysis in our laboratory (45) confirmed the N-terminal modification and the major methylation of Lys-3 as opposed to Lys-10 (53).…”
Section: Protein N-terminal Methyltransferasesmentioning
confidence: 57%
“…By 2006, our laboratory had found evidence for five added methyl groups on the large ribosomal subunit yeast protein Rpl12ab near the N-terminus; modification at Lys-3 by a SET-domain methyltransferase designated Rkm2 and by a yet unidentified enzyme at Lys-10 (44). However, these results were called into question by reports on the modifications of the orthologs of Rpl12ab in Arabidopsis thaliana (51) and Schizosaccharomyces pombe (52); both reports suggested that our mass spectrometry data was more consistent with the dimethylation of the N-terminal proline residue and the trimethylation of Lys-3 in line with the similar N-terminal modification of the Arabidopsis and S. pombe proteins. Further analysis in our laboratory (45) confirmed the N-terminal modification and the major methylation of Lys-3 as opposed to Lys-10 (53).…”
Section: Protein N-terminal Methyltransferasesmentioning
confidence: 57%
“…We conclude that the RPL10B protein has a specific and essential participation during plant growth, which cannot be replaced by the other RPL10 proteins. Moreover, the presence of the RPL10B isoform has not yet been confirmed in the Arabidopsis 80S ribosome, as no specific tryptic peptide from this protein has been identified by MS/MS in survey experiments (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). Alternatively, it cannot be ruled out that RPL10B has extraribosomal functions during development.…”
Section: Discussionmentioning
confidence: 98%
“…Identification of proteins from purified ribosomes by two-dimensional (2D) electrophoretic analyses followed by mass spectrometry (MS) demonstrated the presence of 79 families of ribosomal proteins in the 80S ribosome. Nearly half are represented by two or more protein spots on 2D gels, indicating that proteins are posttranslationally modified and/or present as different isoforms (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). It is hypothesized that this ribosomal heterogeneity fosters selective translation of specific mRNA under particular cell conditions (Barakat et al, 2001;Szick-Miranda and Bailey-Serres, 2001;Giavalisco et al, 2005;Carroll et al, 2008).…”
mentioning
confidence: 99%
“…The specific function of individual cytoskeleton-associated and/or RNA-binding proteins in these processes can only be speculated, although a number of ribosomal and cytoskeletal proteins also belonged among the highest-ranked proteins. Presence of all identified proteins together with great extent of vigorous post-translational modifications of plant ribosomal proteins 71 suggests high regulatory dynamics within EPP complexes, especially during the progamic phase. mRNP particles arranged in higher-order complexes or granules were previously identified in many yeast and animal systems.…”
Section: Honys Et Almentioning
confidence: 99%